Islamic Financial Inclusion in Islamic Bank: A Study of Supply and Demand in Central Java - Mardhiyaturrositaningsih, Mardhiyaturrositaningsih; Janah, Rohmatul (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This study examines the constraints and strategies for enhancing Islamic financial inclusion in Central Java from the perspectives of supply and demand. Using a qualitative descriptive approach, data were collected through Focus Group Discussions with five Islamic Rural Banks (BPRS) and surveys involving 66 MSMEs. Findings reveal seven supply-side constraints, including limited public and human resource literacy, absence of ATMs, restricted branch networks, limited capital, difficulties in customer segmentation, and inadequate socialization efforts. Meanwhile, six demand-side barriers were identified, such as limited awareness of BPRS, perceived complexity in financing requirements, and concerns over collateral and loan repayments. To address these issues, two strategies are proposed: 1) targeted socialization and education campaigns and 2) enhanced collaboration with community organizations and stakeholders. The study underscores the need for joint efforts by BPRS, MSMEs, and the government to improve infrastructure and accessibility, thereby fostering broader Islamic financial inclusion